Acclimatization process of microorganisms from activated sludge in kenaf-retting wastewater - Zainuddin, Zawani; Abdullah, Luqman Chuah; Ahmadun, Fakhru'l-Razi; Abdan, Khalina (Springer, 2013)
Acclimatization process of microorganisms in Kenaf-retting wastewater was studied using return activated sludge (RAS). RAS was collected from near sewage treatment plant. Initial concentration of chemical oxygen demand (COD) in the wastewater and mixed liquor suspended solids (MLSS) of activated sludge were 2,300 and 1,000 mg/l, respectively. The MLSS and COD concentrations were stabilized at day-25th. The highest substrate removal was recorded at 85 %, and it is found that activated sludge bacteria are well adapted in the new environment. At the end of the experiment, microorganisms, namely Achromobacter sp, Bacillus sp and Acinetobacter sp, were found dominated in the wastewater.